1923 Pa. Laws 386, No. 228, art. 7, § 704(a) - (:unkn) unknown (My University, 1923)
. . . It is unlawful to hunt for, or catch or take or kill or wound, or attempt to catch or take or kill or wound, game of any kind, excepting raccoons, through the use of what is commonly known as an automatic gun or an automatic firearm of any kind, or a swivel gun or an air-rifle or the apparatus known as a silencer, or from an automobile or vehicle or boat or craft of any kind propelled by any mechanical power. . .
Keywords: HUNTING REGULATION; MACHINE GUN RESTRICTION; SUPPRESSORS